(3GdeNJGQ ef QSGFd CHj ESMGb GdUGHFs - (3GdUCHjA , CHh ESMGb EHQGgje Hf gdGd Hf EHQGgje Hf RgQhf GdMQGfj GdUGHF,J (B384 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3fSNI cJGH CfTGg CHh ESMGb EHQGgje Hf gdGd GdUGHF YfO aJM HZOGO, hEfgRGe GdCJQGc YfgG aj LeGOj GdChdi s
(3BNQgG (B:s
(3adjS jLQhf eY ChdFc aj eVeGQ, h jbGQHhge aj GdCbOGQ, hgPG bhd cGa ajeG COQfGg Je GdeNJGQ ef QSGFd s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B24 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs